1997
DOI: 10.1152/ajplung.1997.272.1.l15
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced goblet cell hypersecretion in the guinea pig trachea: inhibition by macrolides

Abstract: We studied the effects of macrolides on lipopolysaccharide (LPS)-induced airway goblet cell secretion in the guinea pig trachea. The goblet cell secretion was assessed in histological sections of the tracheal mucosa stained with alcian blue and periodic acid Schiff by arbitrarily determining mucus score, which is inversely related to the magnitude of mucus discharge. Inhalation of Escherichia coli LPS (5 mg/kg) caused a time-dependent decrease in mucus score, with the maximal response being from 542 +/- 49 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…In addition, the time to successful discontinuation of mechanical ventilation was shorter in participants given macrolides, compared with participants not receiving macrolides (adjusted hazard ratio [HR] for successful ventilator models suggest a therapeutic role for macrolide antibiotics in ALI. [14][15][16][17][18][19][20] We sought to investigate the association between macrolide antibiotics and mortality in patients with ALI using data from the Acute Respiratory Distress Syndrome Network (ARDSNet) Lisofylline and Respiratory Management of Acute Lung Injury (LARMA) trial. 8 We hypothesized that use of macrolide antibiotics would be associated with reduced mortality in patients with ALI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the time to successful discontinuation of mechanical ventilation was shorter in participants given macrolides, compared with participants not receiving macrolides (adjusted hazard ratio [HR] for successful ventilator models suggest a therapeutic role for macrolide antibiotics in ALI. [14][15][16][17][18][19][20] We sought to investigate the association between macrolide antibiotics and mortality in patients with ALI using data from the Acute Respiratory Distress Syndrome Network (ARDSNet) Lisofylline and Respiratory Management of Acute Lung Injury (LARMA) trial. 8 We hypothesized that use of macrolide antibiotics would be associated with reduced mortality in patients with ALI.…”
Section: Resultsmentioning
confidence: 99%
“…the use of macrolide therapy in community-acquired pneumonia, 11 ventilator-associated pneumonia, 29 diffuse panbronchiolitis, 12 and cystic fi brosis. 13 Specifi cally, the pleiotropic antiinfl ammatory activities of macrolides include attenuation of pulmonary epithelial cell nuclear factor-k B activity, 30 decreased survival 31 and oxidative burst 32 of activated neutrophils, reduced endotoxin-induced goblet cell hypersecretion, 18 and inhibition of immune-complex-induced lung injury. 17 The potential therapeutic value of the antiinfl ammatory effects of macrolides is supported by observations in murine models of ALI caused by endotoxin, 16,19 infl uenza, 14 or bleomycin, 15,20 which have demonstrated less severe injury and increased survival with macrolide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the effect of macrolide treatment on mucus secretion, previous studies reported that erythromycin inhibits respiratory glycoconjugate secretion from human airways in vitro (12) and reduced mucin secretion from cultured guinea pig epithelial cells (33). However, to our knowledge, there are no studies that have previously analyzed the effect of macrolides on mucin core proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Erythromycin was also reported to attenuate bronchial hyperresponsiveness in patients with bronchial asthma, probably through its inhibitory action on superoxide production and chemotaxis of neutrophils [32]. Erythromycin may also be helpful in asthma management, through protection of the ciliated airway epithelium from the action of bioactive phospholipids [33], reduction of mucus production [34] and improvement of the biophysical properties of mucus [35]. Finally, it has been suggested that erythromycin inhibits glucocorticoid clearance and enhances the effect of steroid therapy on asthma [36].…”
Section: Discussionmentioning
confidence: 99%